Diversidad florística y estructura del bosque secundario en la hacienda PB54 de la empresa Plantabal S.A., Cantón La Maná, Provincia de Cotopaxi. - Chávez Rivera, Miryan Melina (2020)
The research project was carried out at the property of the company PLANTABAL S.A., located in the Poza Honda sector, La Maná canton, Cotopaxi province. The objective was to evaluate the floristic diversity and structure of the secondary forest on the PB54 farm. Fifteen 400 m 2 random sampling units were established. In each plot, an inventory of trees with a DBH ≥ of 7.5 cm was made, recording the common name, characteristics and height of the species. Diversity, dominance and similarity indices were evaluated, as well as the Importance Value Index (IVI) and Forest Value Index (IVF). A total of 341 individuals belonging to 20 families, 29 genera and 30 species were found, the most important families being Moraceae with 3 species, Leguminosae with 2 species, Rubiaceae with 2 species and Solanaceae with 2 species. The Importance Value Index (IVI) indicated that the most representative species were Aegiphila alba (Lulo) with 36.80%, followed by Castilla elastica (Caucho) with 13.61% and Cecropia peltata (Guarumo) with 11.91%. Shannon's highest diversity index was 1.911, indicating that plot 3 obtained high species diversity, while Simpson's dominance index was 0.833, showing that plot 2 had the highest dominance, while Jaccard's similarity index among the sampling units indicated 63% of similarity among species. In the diameter distribution, the largest number of individuals (145) were concentrated in the diameter class II (10 - 19.99 cm). The general distribution shows the shape of the inverted J-curve and the sociological position of the heights among the specimens did not exceed 28 m in height. The recorded species were not found in the IUCN list, due to not being registered (NE). ABSTRACT Keywords: Floristic diversity, structure, indices, sampling unit, species.